Tunga (halved) - Lozada, MA Theodore F. 1992-; Lejano, Eduardo J.; University of the Philippines. College of Mass Communication (2013)
"Tunga is an eighteen minute short film that explores the question of identity, of Self and the Other and how one should define the Filipino. It draws on Edward Said's theory of the Other and Jacques Lacan's theory of the formation of identity as it follows a father and son, the former who has given up hope of reconciliation and the latter who defies what his father has taught him of what the Self should be."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Self